Assessment of common ground improvement methods on the unliquefiable soil layer in mitigating liquefaction-induced settlement - Malonzo, Marvin Renzo B.; Marcelino, Ma. Nicole Ann P.; Acacio, Alexis A.; Zarco, Mark Albert H. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Among the many consequences brought about by an earthquake, settlement due to liquefaction is an effect that imposes damage to infrastructures. For infrastructures with deep foundation systems, liquefaction-induced settlement would be less likely to occur. However, this is not the case for areas with soft and weak soils and shallow foundations. In order to minimize damage and avoid the high cost of deep foundation systems, it is helpful to determine the suitable ground improvement methods that would complement the use of shallow foundations. This study aims to determine which ground improvement methods would minimize the settlement due to liquefaction by the simulation of an earthquake and liquefaction phenomenon in a shaking box. The ground improvement techniques analyzed are vibroflotation, compaction pile method, gravel mixture and use of tire chips. The results demonstrated that the chosen ground improvement methods applied on the soil layer above the groundwater table are effective at mitigating liquefaction-induced settlement brought about by earthquakes of magnitude 5.0 to 5.9. Among the ground improvement methods considered, the use of tire chips proved to be the most effective. Moreover, this study was able to prove that with the appropriate ground improvement technique, liquefaction-induced settlement can be mitigated even if the thickness of the unliquefiable layer is relatively less than that of the underlying liquefiable soil.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Soil liquefaction; Soil stabilization -- Testing